Legal Criticism Of The Code Of Law The New Criminal Law Is Viewed From The Point Of View Philosophical, Sociological And Juridical - Soedirjo, Achmad Taufan; Jaya, Surya (Journal of Social Research, 2023)
The need for a new National Criminal Code is based on philosophical, sociological, and legal considerations, among others: "(1) the view of life, level of awareness, and legal ideals derived from Pancasila and the Preamble of the 1945 Constitution; (2) paying attention to the needs of society and the state towards the development of empirical facts of national criminal law; and (3) paying attention to pre-existing racial and ethnic inequalities." The purpose of this study is to determine the extent to which the newly passed Criminal Code (KUHP) is able to accommodate the problems of criminal acts that occur in Indonesia in particular and matters related to cross-border criminal acts. The research method used is normative research with a legal approach and conceptual approach. The results of the discussion show that the new Criminal Code is considered not to provide fair law enforcement against perpetrators of criminal acts, especially related to discrimination against minority groups and violence against women. The new Criminal Code is considered not accommodating technological developments and social progress, so it is unable to provide appropriate solutions to technology-related criminal offenses. The new Criminal Code is considered to not provide fair law enforcement against perpetrators of criminal offenses who have high power or position, such as politicians or high-ranking officials. The new Criminal Code is considered not providing the right solution to criminal offenses related to social problems, such as drugs, corruption, and domestic violence.